Case study of Markov modeling for safety analysis - Xu, Ming Shan. (2008)
This dissertation deals with the evaluation of safety integration level of a process shutdown system for a compressor of a liquefied natural gas (LNG) plant. The process shutdown system (PSS) detects some critical process variables which while rising to a certain limiting value will endanger the compressor and the personnel. Hence PSS protects the compressor by shutting it down. In the process control industry, often there is a need to analyze and demonstrate that the PSS meets the safety integrity level (SIL) requirement that was specified by the customer in the tender document.